1989
DOI: 10.1007/bf00441940
|View full text |Cite
|
Sign up to set email alerts
|

Long-term lithium treatment in rats attenuates m-chlorophenylpiperazine-induced decreases in food intake but not locomotor activity

Abstract: Administration of various doses of m-chlorophenylpiperazine (m-CPP, a 5-HT agonist) to rats produced dose-related decreases in food intake and locomotor activity. Long-term (21-25 days) but not short-term (3-7 days) lithium treatment attenuated m-CPP-induced decreases in food intake. However, neither short-term nor long-term lithium treatment had any significant effect on m-CPP-induced decreases in locomotor activity. These findings suggest development of functional subsensitivity of 5-HT1B receptors mediating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1

Year Published

1990
1990
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
2
9
1
Order By: Relevance
“…tryptamine (5-HT) releasing agent fenfluramine (Hewson et al, 1988), the 5-HT1J5-HT2 agonists DOI (Schechter & Simansky, 1988) and quipazine (Hewson et al, 1989) have all been interpreted in terms of activation of 5-HT2 receptors. Also, other reports suggest that the effect of TFMPP is 5-HT2-mediated (Klodzinska & Chojnacka-Wojcik, 1990) and that the action of mCPP might not be 5-HT1c-dependent (Aulakh et al, 1989). These apparent conflicts with our findings may derive from experimental differences and from the customary use of in vitro affinity constants of antagonists as indices of receptor blockade in vivo.…”
contrasting
confidence: 92%
See 1 more Smart Citation
“…tryptamine (5-HT) releasing agent fenfluramine (Hewson et al, 1988), the 5-HT1J5-HT2 agonists DOI (Schechter & Simansky, 1988) and quipazine (Hewson et al, 1989) have all been interpreted in terms of activation of 5-HT2 receptors. Also, other reports suggest that the effect of TFMPP is 5-HT2-mediated (Klodzinska & Chojnacka-Wojcik, 1990) and that the action of mCPP might not be 5-HT1c-dependent (Aulakh et al, 1989). These apparent conflicts with our findings may derive from experimental differences and from the customary use of in vitro affinity constants of antagonists as indices of receptor blockade in vivo.…”
contrasting
confidence: 92%
“…The failure of Aulakh et al (1989) (and RU 24969) and hence possibly also to their antagonists, than when food-deprived animals are used as in the present study (Table 3). A similar argument may also explain why doses of ketanserin and ritanserin needed to antagonize hypophagias induced by fenfluramine (Hewson et al, 1988), quipazine (Hewson et al, 1989) and DOI (Schechter & Simansky, 1988) were less than those we found to inhibit Kennett et al (1987) and Kennett & Curzon (1988a) expressed as percentages and Arcsin-transformed (Winer, 1971) as outlined by Bowman & Rand (1980).…”
Section: Discussionmentioning
confidence: 85%
“…However, this possibility is unlikely since long-term lithium treatment did not potentiate fenfluramine's effect on food intake in the present study. Furthermore, we have demonstrated in a previous report from this laboratory that similar short-term lithium treatment did not potentiate m-chlorophenylpiperazine (m-CPP, a post-synaptic 5-HT, receptor agonist)-induced decreases in food intake (Aulakh et al, 1989). However, long-term (2-3 weeks) lithium treatment causes down-regulation of 5-HTl and 5-HT2 receptors in the cortex, hippocampus and striatum (Hotta, Yamawaki and Segawa, 1986;Maggi and Enna, 1980;Treiser and Kellar, 1980), decreases activity of the synthetic enzyme, tryptophan hydroxylase (Knapp and Mandell, 1973), desensitizes 5-HT autoreceptors mediating 5-HT release (Wang and Friedman, 1988) and attenuates m-CPP-induced decreases in food intake (Aulakh et al, 1989).…”
Section: Discussionmentioning
confidence: 69%
“…Physi ological effects of MCPP are reduced by chronically administered antidepressants. For example, MCPP-induced hypophagia in rats is blunted by chronic lithium or clorgyline [27,28], and its hyperthermic effects are re duced by chronic clorgyline, chlorimipramine and imipramine [29]. MCPP-induced loco motion is attenuated by chronic clorgyline [28] and is increased by chronic imipramine [30], Hence, it is likely that metabolic toler ance to MCPP found in this study is due to downregulation of presynaptic 5-HT recep tors at which MCPP acts.…”
mentioning
confidence: 66%